2019
DOI: 10.3390/plants8060166
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Adult Functional Traits of Local Populations and Cultivars of Sandberg Bluegrass and Bottlebrush Squirreltail Perennial Bunchgrasses

Abstract: Plant functional traits offer an understanding of the plant’s ability to cope with varying environmental impositions. The objective of this study was to evaluate the above and belowground adult morphological and chemical composition traits of local populations of Sandberg bluegrass (Poa secunda J. Presl) and Bottlebrush squirreltail (Elymus elymoides (Raf.) Swezey) collected in Nevada and their cultivated varieties. A total of six replications (one seedling each) from each population and cultivar of the two na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…While it is clear that the process of plant selection and commercial production for restoration can impact both trait values and variation relative to wild populations, studies to date have largely focused on changes in aboveground traits. Of the few studies available, one found little evidence for root trait differences between cultivar and wild‐collected accessions in two grass species native to the western United States ( Poa secunda and Elymus elymoides ), despite substantial differences in aboveground biomass (Solomon 2019). Conversely, a study of two grass species native to the tallgrass prairies of North America ( Sorghastrum nutans and Schizachyrium scoparium ) found that cultivars had larger root systems and used more nitrogen than wild‐collected accessions, while no differences were detected in shoot traits between collection types (Klopf & Baer 2011).…”
Section: Introductionmentioning
confidence: 99%
“…While it is clear that the process of plant selection and commercial production for restoration can impact both trait values and variation relative to wild populations, studies to date have largely focused on changes in aboveground traits. Of the few studies available, one found little evidence for root trait differences between cultivar and wild‐collected accessions in two grass species native to the western United States ( Poa secunda and Elymus elymoides ), despite substantial differences in aboveground biomass (Solomon 2019). Conversely, a study of two grass species native to the tallgrass prairies of North America ( Sorghastrum nutans and Schizachyrium scoparium ) found that cultivars had larger root systems and used more nitrogen than wild‐collected accessions, while no differences were detected in shoot traits between collection types (Klopf & Baer 2011).…”
Section: Introductionmentioning
confidence: 99%
“…P . secunda variability in response to temperature (Monaco et al, 2005), tree cover, and added resources among sites (Bates et al, 2000; Williams et al, 2017) may be associated with its ecotypic variation (Solomon, 2019), and could explain the lack of response to early spring water in our model.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, we found a negative association between pretreatment phosphorous and posttreatment cover of P. secunda (Figure 3), supporting Aanderud et al (2017), who reported a negative association between phosphorous and P. secunda cover after tree mastication. P. secunda variability in response to temperature (Monaco et al, 2005), tree cover, and added resources among sites (Bates et al, 2000;Williams et al, 2017) may be associated with its ecotypic variation (Solomon, 2019), and could explain the lack of response to early spring water in our model.…”
Section: Early Spring Water and Grassesmentioning
confidence: 98%
“…Maize yields were not satisfactory without groundcover suppression when using fescue, even under irrigation (Carreker et al., 1972). Significant genetic variation exists among cultivars, accessions, and populations for Kentucky bluegrass (Honig et al., 2012; Wieners et al., 2006), red fescue (Wang et al., 2017) and Sandberg bluegrass (Johnson et al., 2015; Solomon, 2019). Therefore, screening wild or unimproved accessions of Kentucky bluegrass, red fescue, and Sandberg bluegrass may allow identification of suitable candidates for perennial groundcovers and to inform grass breeders of traits or trait combinations that are important for perennial groundcovers.…”
Section: Introductionmentioning
confidence: 99%